2021
DOI: 10.1021/acs.energyfuels.1c03132
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Dependent Unstable Dynamic Propagation of Three-Dimensional Multiple Hydraulic Fractures with Improved Fracturing Sequences in Heterogeneous Reservoirs: Numerical Cases Study via Poroelastic Effective Medium Model

Abstract: Multistage hydrofracturing of horizontal wells is one of the key technologies for deep tight oil and gas resource exploitation. The stable and parallel propagation of multiple fractures formed by multistage perforation cluster fracturing is conducive to the formation of a developed fracture network. However, in the actual process of rock fracturing in deep tight reservoirs, owing to the influence of many factors, such as fracturing sequence, perforation cluster space, reservoir heterogeneity, and stress shadow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…With a decrease in the perforation cluster space, the fracture was more prone to deflection and the degree of deflection was greater. In the case of larger spacing between perforation clusters, the three fractures propagate almost in a straight plane (Li et al, 2019b;Wang and Liu, 2021;Escobar et al, 2019;Liu et al, 2020). Reducing cluster spacing can increase hydraulic fracture complexity and improve horizontal well productivity (Luo et al, 2021).…”
Section: Review Of Stress Shadow and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With a decrease in the perforation cluster space, the fracture was more prone to deflection and the degree of deflection was greater. In the case of larger spacing between perforation clusters, the three fractures propagate almost in a straight plane (Li et al, 2019b;Wang and Liu, 2021;Escobar et al, 2019;Liu et al, 2020). Reducing cluster spacing can increase hydraulic fracture complexity and improve horizontal well productivity (Luo et al, 2021).…”
Section: Review Of Stress Shadow and Methodsmentioning
confidence: 99%
“…In the case of larger spacing between perforation clusters, the three fractures propagate almost in a straight plane (Li et al. , 2019b; Wang and Liu, 2021; Escobar et al. , 2019; Liu et al ., 2020).…”
Section: Unstable Dynamic Propagation Behaviours Of the Multistage Hy...mentioning
confidence: 99%
“…Other studies using this model also found that the deflection behaviours of fractures depended on the heterogeneity of rock mass and the distribution of natural fractures. This will change the varying range and area of stress in the reservoir rock, thus affecting the initiation and propagation of fractures (Wang and Liu, 2021; Wang et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The decrease in perforation cluster spacing increases the possibility of fracture deflection, and the degree of deflection is greater. Parallel fractures propagate almost in a straight plane with large perforation cluster spacing [14][15][16][17]. Deflection of hydraulic fractures and evolution of stress fields under various initial perforation forms become important factors affecting fracture network morphology and fracturing effects [14,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…In simultaneous fracturing, fracture propagation in the middle is inhibited and shorter than that on both sides [15,24,25]. The optimal cluster spacing for alternate fracturing is almost half that of sequential fracturing, and alternate fracturing leads to more fractures [15,17,26].…”
Section: Introductionmentioning
confidence: 99%